Understanding climate's influence on the extinction of Oreopithecus (late Miocene, Tusco-Sardinian paleobioprovince, Italy). Issue 116 (March 2018) - DeMiguel, Daniel; Rook, Lorenzo
Abstract: Despite its long history of scientific study, the causes underlying the extinction of the insular hominoid Oreopithecus bambolii are still a matter of ongoing debate. While some authors consider intense tectonism and invading species the cause of its extinction ca. 6.7 Ma, others propose climatic change as the main contributing factor. We rely on long-term patterns of tooth wear and hypsodonty of the Baccinello and Fiume Santo herbivore-faunas to reconstruct changes in habitat prior to, during and after the extinction. While a mosaic of habitats was represented in Baccinello V1 (as shown by a record of browsers, mixed feeders and species engaged in grazing), more closed forests (higher proportion of browsers, shortage of mixed feeders and lack of grazers) characterised Baccinello V2. Finally, there was a partial loss of canopy cover and development of open-patches and low-abrasive grasses in Baccinello V3 (as denoted by new records of taxa involved in grazing)—although still dominated by a forested habitat (since browse was a component in all diets). Our results provide evidence for two perceptible shifts in climate, one between 8.1 and 7.1 Ma and other ca. 6.7 Ma, though this latter was not drastic enough to lead to intensive forest loss, substantially alter the local vegetation or affect Oreopithecus lifestyle—especially if considering the growing evidence of its versatile diet. Although the disappearance of Oreopithecus is complex, our data reject the hypothesis of environmental change as the main factor in the extinction of Oreopithecus and Maremma fauna. When our results are analysed together with other evidence, faunal interaction and predation by invading species from mainland Europe seems to be the most parsimonious explanation for this extinction event. This contrasts with European hominoid extinctions that were associated with major climatic shifts that led to environmental uniformity and restriction of the preferred habitats of Miocene apes.